Perubahan Peran Suami dan Isteri dalam Keluarga di Desa Molinese Kecamatan Lainea Kabupaten Konawe Selatan - Muhamad Al Kausar; Desrianti Desrianti (Jurusan Antropologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2024)
The purpose of this research is to find out how the roles of husbands and wives in the family and what the implications of changes in the roles of husbands and wives are for the family. The selection of informants in this study used the purposive sampling technique . This research uses the Theory of Social Change by William F. Ogburn. The data collection technique used in this research is field work using two methods, namely observation and in-depth interviews. This research is qualitative research using ethnographic research methods. The results of this study show that, role change in Molinese Village has slowly occurred in the 2000s and above and there are several families who experience it because of the lack of income in the family so that it affects the economy. However, with the entry of the oil palm company in this village in 2007, immediately the wives flocked to work as employees of the oil palm plantation as well as the husbands, but over time many husbands stopped working because of the wage system that was considered uneven and they chose to do gardening and some did not have a permanent job. Meanwhile, the wives are still working as employees of the oil palm plantation or PT MERBAU, until now. Some of the implications of changes in the role of husbands and wives on the family are the lack of harmony in the household, not having a tire, and the lack of a permanent job.